Reenvisioning postpandemic youth sport to meet young people`s mental, emotional, and social needs - Whitley, M. A.; Smith, A. L.; Dorsch, T. E.; Bowers, M. T.; Centeio, E. E. (Translational Journal of the American College of Sports Medicine, 2021)
Before 2020, young people were experiencing significant psychosocial challenges, with the COVID-19 pandemic and related events (e.g., lockdowns, social isolation, and economic disruption) amplifying concerns about their well-being. Youth sport is a context for promoting mental, emotional, and social health, and yet it is not achieving its full potential in the United States. The purpose of this expert commentary, composed by the 2020-2021 President`s Council on Sports, Fitness & Nutrition Science Board, is to present a vision of youth sport in the United States that prioritizes young people`s mental, emotional, and social health. The extraordinary events of 2020 and 2021 provide an opportunity to reenvision our approach to youth sport as pandemic-related restrictions are lifted. Ten recommendations from this vision are presented in this article, along with 10 innovative, actionable takeaways; each of these offer meaningful benefits to young people`s mental, emotional, and social health.